Analysis of Cesarean Section Rates Based on ROBSON Classification System in a Tertiary Care Hospital in West Coast of Gujarat, India - Punatar, Dr. Preeti; Pattani, Dr. Bhakti (International Journal of Innovative Research in Medical Science, 2023)
Background with objectives: Because of growing concern over the increasing C-Section worldwide, WHO proposes the ROBSON classification system as a global standard for assessing, monitoring and comparing caesarean section rates. Objective of present study is to investigate CS rates according to ROBSON classification system and to determine area of concern to decrease overall C-section rates. Methods: This study is a retrospective descriptive cohort study done with all caesarean sections delivered in a tertiary teaching hospital in the west coast of Gujarat, India from January 2022 to December 2022. Results: In current study, total CS rate was 28.47%. The major contributor to total CS rate was ROBSON I group (34.09%) followed by ROBSON V (26.34%). Major indications for ROBSON I group include fetal distress due to meconium-stained liquor (25%), Cephalo-pelvic disproportion (CPD) stage1(18%). Major indications for ROBSON group V includes CPD 1(31%), scar tendereness(23%) and previous 2 LSCS(14%). Conclusion: ROBSON I and V being major contributors to total CS suggest to focus on these groups to reduce total CS rate. Art of proper labor monitoring is to be rejuvenated to reduce ROBSON I group, more trial of labor after cesarean should be performed to reduce ROBSON V group.